2010
DOI: 10.1111/j.1095-8649.2009.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate comparison of the stress response in three salmonid and three cyprinid species: evidence for inter‐family differences

Abstract: The response of six species of freshwater fishes, from the families Cyprinidae (common carp Cyprinus carpio, roach Rutilus rutilus and chub Leuciscus cephalus) and Salmonidae (rainbow trout Oncorhynchus mykiss, brown trout Salmo trutta and Arctic charr Salvelinus alpinus), to a standardized stressor was evaluated. A 6 h period of confinement resulted in changes to plasma cortisol, glucose, amino acid and lactate levels compared with unconfined controls. There were significant differences in the response profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 120 publications
(183 reference statements)
3
40
3
1
Order By: Relevance
“…Both basal and stressed cortisol levels differ widely between species, and within a species (Fig. 2), being affected by factors such as temperature, gender, sexual maturity and genetics (Pottinger 2010). Barton (2002) showed that both basal and stressed cortisol levels differed between species of fish exposed to an identical procedure (30 s aerial emersion).…”
Section: Variability In Basal and Response Levelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both basal and stressed cortisol levels differ widely between species, and within a species (Fig. 2), being affected by factors such as temperature, gender, sexual maturity and genetics (Pottinger 2010). Barton (2002) showed that both basal and stressed cortisol levels differed between species of fish exposed to an identical procedure (30 s aerial emersion).…”
Section: Variability In Basal and Response Levelsmentioning
confidence: 97%
“…The main difference between the catecholamines and cortisol is that the release of catecholamines is triggered by nerve circuitry (rather than by a cascade of chemical messengers) so the response is very quick, making it virtually impossible to obtain baseline blood concentration unaffected by the sampling itself. Catecholamines in fish have therefore received much less attention than cortisol but merit greater investigation (Pottinger 2010). …”
Section: What Is Stress?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hormones were dissolved in appropriate solutions and stored as single use stock aliquots at -30°C until use. Cortisol was used at a single dose of 500ngml -1 , which was selected based on the response of cultured trout gill epithelia to cortisol treatment as observed in previous studies (Chasiotis et al, 2010;Kelly and Wood, 2001) as well as levels of cortisol seen in stressed salmonids (see Pottinger, 2010). Deoxycorticosterone and aldosterone were used at doses of 5, 50 and 500ngml -1 and dexamethasone was used at a final concentration of 1.4mmoll -1 (i.e.…”
Section: Hormones and Pharmacological Agentsmentioning
confidence: 99%
“…Examples include suboptimal/poor water quality, repeated handling, transport and crowding. The effects of many of these challenges have been studied, albeit mostly as a single stressor (Barton and Peter, 1982;Gorissen et al, 2012;Di Marco et al, 2008;Pottinger, 2010;Remen et al, 2012). Studies on mammals (Aguilera and Rabadan-Diehl, 2000;Dhabhar and McEwen, 1997;Grissom and Bhatnagar, 2009;Thorsell et al, 1999), as well as fish (Schreck, 2000), show they have great resilience to a single stressor given repeatedly over long periods of time; however, knowledge on how ectotherms respond to multiple persistent stressors is very scant.…”
Section: Introductionmentioning
confidence: 99%